Hibah dengan Kompensasi Perspektif Fukaha Klasik dan Kontemporer - Waluya, Atep Hendang (Al-Muzdahir : Jurnal Ekonomi Syariah, 2025)
The transfer of property ownership is currently mostly done through contracts, among the contracts used for the transfer of property ownership is the grant contract. One form of the grant (hibah) is that the giver (wāhib) requires compensation. The existence of this compensation causes differences regarding the permissibility of the grant and whether it is in the form of a grant or a sale. According to the Hanafi, Maliki, Hanbali schools and the strongest opinion in the Syafi'i school, a gift with compensation conditions is valid and its law is the law of sale. Among the contemporary jurists who believe that a gift contract with compensation is a sale and purchase are Al-Dubyān, Al-Qalīṣī, Aḥmad Sa'ād, Muḥammad al-Zuḥaylī, al-Khin, al-Bughā and al-Sharbazī. Their reason is that the contract looks at the purpose and meaning, not at the wording. According to Al-Qalīṣī, Muḥammad al-Zuḥaylī, al-Khin, al-Bughā and al-Sharbazī, that a grant with compensation conditions if the compensation is not determined and is not known then the contract is invalid and this is the most valid opinion in the Syafi'i School and the strongest in the Hanbali School.